2016
DOI: 10.1088/1475-7516/2016/01/041
|View full text |Cite
|
Sign up to set email alerts
|

Scale-dependent gravitational waves from a rolling axion

Abstract: Abstract. We consider a model in which a pseudo-scalar field σ rolls for some e-folds during inflation, sourcing one helicity of a gauge field. These fields are only gravitationally coupled to the inflaton, and therefore produce scalar and tensor primordial perturbations only through gravitational interactions. These sourced signals are localized on modes that exit the horizon while the roll of σ is significant. We focus our study on cases in which the model can simultaneously produce (i) a large gravitational… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
372
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(389 citation statements)
references
References 125 publications
(278 reference statements)
12
372
0
Order By: Relevance
“…Thus n T > 0 requires either the superinflation [9][10], also [11] [12], which breaks the null energy condition (NEC), or an anisotropic stress source during inflation, e.g., the particle production [13] [14][15] [16]. During the superinflation, the primordial GWs come from the amplification of vacuum tensor perturbations.…”
Section: Introductionmentioning
confidence: 99%
“…Thus n T > 0 requires either the superinflation [9][10], also [11] [12], which breaks the null energy condition (NEC), or an anisotropic stress source during inflation, e.g., the particle production [13] [14][15] [16]. During the superinflation, the primordial GWs come from the amplification of vacuum tensor perturbations.…”
Section: Introductionmentioning
confidence: 99%
“…Some criticism on this model have raised due to the validity of its perturbative expansion and about the consistency of this mechanism to produce sizable primordial gravitational waves without contradict current observational limits [69,70]. Nevertheless, by using the perturbative approach, it was shown that the model have an available parameter window, that is in agreement with the current observational constraints [55,71].…”
Section: Perturbative Expansionmentioning
confidence: 89%
“…We consider a scenario with a scalar field driving the inflationary expansion, and a vector field, which is partly responsible fro the generation of the primordial curvature perturbation and is a source of statistical anisotropies. Several models of this type has been studied in the literature [32,35,37,38,40,[43][44][45][46][47][48][49][50][51][52][53][54][55][56]. The interest for those models has been diverse and it has evolved over the years.…”
Section: A Parity Violating Scalar-vector Inflationary Modelmentioning
confidence: 99%
See 2 more Smart Citations